Prevalence and associated factors of active trachoma among 1-9 years of age children in Andabet district, northwest Ethiopia, 2023: A multi-level mixed-effect analysis. - Zufan Alamrie Asmare; Beminate Lemma Seifu; Kusse Urmale Mare; Yordanos Sisay Asgedom; Bizunesh Fantahun Kase; Abdu Hailu Shibeshi; Tsion Mulat Tebeje; Afework Alemu Lombebo; Kebede Gemeda Sabo; Bezawit Melak Fente; Achamyeleh Birhanu Teshale; Hiwot Altaye Asebe (Public Library of Science (PLoS), 2023)
Background Trachoma is the chief cause of preventable blindness worldwide and has been earmarked for elimination as a public health problem by 2030. Despite the five-year Surgery, Antibiotics, Facial cleanliness, and Environmental improvement (SAFE)-based interventions in the Andabet district, the prevalence of trachomatous follicular (TF) was 37%. With such a high prevalence of TF, the determinant factors were not revealed. Besides, there were no reports on the overall prevalence of active trachoma (i.e.TF and or trachomatous intense (TI)). Objective To determine the prevalence and associated factors of active trachoma among 1-9 years of age children in the Andabet district. Method A community-based cross-sectional study was conducted among children aged under nine years from March 1-30, 2023 in Andabet district, Northwest Ethiopia. Multi-stage systematic random sampling was employed to reach 540 children. A multilevel mixed-effect logistic regression analysis was employed to assess factors associated with active trachoma. We fitted both random effect and fixed effect analysis. Finally, variables with p<0.05 in the multivariable multilevel analysis were claimed to be significantly associated with active trachoma. Result In this study, the overall prevalence of active trachoma was 35.37% (95% CI: 31.32%, 39.41%). The prevalence of TF and TI was 31.3% and 4.07% respectively. In the multilevel logistic regression analysis ocular discharge, fly-eye contact, latrine utilization, and source of water were significantly associated with the prevalence of active trachoma. Conclusion In this study, the prevalence of active trachoma was much higher than the World Health Organization (WHO) threshold prevalence. Ocular discharge, fly-eye contact, latrine utilization, and source of water were independent determinants of active trachoma among children (1-9 years). Therefore, paying special attention to these high-risk groups could decrease the prevalence of a neglected hyperendemic disease, active trachoma.